PENGARUH PENERAPAN GOOD GOVERNANCE DAN STANDAR AKUNTANSI PEMERINTAH TERHADAP AKUNTABILITAS KEUANGAN KECAMATAN DI KABUPATEN BARITO KUALA - yudi rahman (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
This study aims to determine and analyze the effect simultaneously and partially of the Implementation of Good Governance and Government Accounting Standards on District Financial Accountability in Barito Kuala Regency. The type of research used by researchers is quantitative research. Quantitative research is carried out by statistical means, namely analyzing with various statistical bases by reading available tables, graphs or figures and then conducting several descriptions or interpretations of the data. To determine the method of data analysis, it can be seen from the objectives and types of research carried out and the existing data models. Data collection techniques are in the form of documentation, investigating written objects such as books, magazines, journals and others, in order to get references to become the basis from research. The results of this study indicate the Simultaneous Implementation of Good Governance and Government Accounting Standards on Subdistrict Financial Accountability in Barito Kuala Regency. The variables of Good Governance Implementation have a significant effect on the Subdistrict Financial Accountability in Barito Kuala Regency partially. Government Accounting Standards variables have a significant effect on Financial Accountability District In Barito Kuala Regency partially. Keywords: Good Governance Implementation, Government Accounting Standards, Financial Accountability